Erratum: Infection 2004; 32: 210-216 (DOI 10.1007/s15010-004-3167-0) (Infection, 2004)
PURPOSE: Although indications for anti-interleukin 6 (IL-6) receptor antibody (anti-IL6R) therapy continue to expand, the clinical features of bloodstream infection (BSI) in anti-IL6R recipients remain poorly characterized. We investigated the prevalence, clinical and microbiological features of BSI among the anti-IL6R recipients. METHODS: We conducted a multicenter, retrospective study of BSI episodes occurring within 90 days of anti-IL6R administration between 2005 and 2024. Complicated BSI was defined as the presence of either (1) infection-related mortality, (2) remote or localized suppurative complications, (3) embolic stroke, or (4) recurrence within 90 days. Associations between clinical variables and complicated BSI were analyzed. RESULTS: Among 922 anti-IL6R recipients, 47 patients (5%) developed BSI. Demographics varied by indication for anti-IL6R, and 89% received concomitant immunosuppressive therapy. Catheter-related bloodstream (23%) and intra-abdominal (21%) were most common foci, followed by bone and joint (14%). At presentation, fever was absent in 53%, and serum CRP was within normal range in 30%. Septic shock occurred in 26%, and all-cause 30-day mortality was 19%. Complicated BSI occurred in 22 episodes (47%). In univariate analysis, underlying rheumatic disease, community acquisition, onset within 21 days of anti-IL6R administration, and Staphylococcus aureus or Klebsiella pneumoniae etiology were associated with complicated BSI, whereas higher pulse rate at presentation and Pitt bacteremia score ≥ 4 were inversely associated. CONCLUSIONS: In anti-IL6R recipients, BSI frequently lacked typical signs such as fever but often resulted in severe outcomes. Clinicians should maintain a high index of suspicion for complicated BSI in this population.